Weed management practices: there influence on weed control, nutrient removal and yield of soybean crop - Singh, S.P.; Singh, J.P.; Bhatnagar, Amit; Kumar, Amit; Yadav, Ajit; Kumari, Usha; Verma, Gaurav (Annals of Agricultural Research, 2017)
A field experiment was conducted during kharif season of 2014 at N. E. Borlaug Crop Research Centre of G. B. Pant University of Agriculture & Technology, Pantnagar (Uttarakhand) to find out the weed management practices: there influence on weed control, nutrient removal and yield of soybean crop. The experiment was laid out in a randomized block design with four replications to evaluate ten treatments viz. sulfentrazone 48% SC @ 300 g a.i/ha pre-emergence (PE), sulfentrazone 48% SC @ 360 g a.i/ha (PE), sulfentrazone 48% SC @ 360 g a.i/ha (PE) + hand weeding (HW) at 40 DAS, sulfentrazone 48% SC @ 300 g a.i/ha (PE) + HW at 40 DAS, pendimethalin 30 EC @ 750 g a.i/ ha (PE), pendimethalin 30 EC @ 1000 g a.i/ha (PE), pendimethalin 30 EC @ 750 g a.i/ha (PE) + HW at 40 DAS and pendimethalin 30 EC @ 1000 g a.i/ha (PE) + HW at 40 DAS, weed free (Hand weeding as and when required) and weedy check. Weed free plot recorded higher grain yield and weed control efficiency (WCE) followed by PE application of sulfentrazone 48% SC @ 360 g a.i/ha + HW at 40 DAS. The lowest total number of weeds, lowest total dry weight of weeds, nutrients removal by weeds and weed index was recorded under PE application of sulfentrazone 48% SC @ 360 g a.i/ ha + HW at 40 DAS. PE application of sulfentrazone 48% SC @ 360 g a.i/ha + HW at 40 DAS could be the recommended weed control option for managing weeds in soybean crop.